A Study of Unveiling the Effect of Perceived Quality, Safety, and Destination Image on Visitor Satisfaction and Return Intentions, Thailand - Prasitvipat, Ratanawalai; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – This study aims to explore the factors influencing tourists’ perceived quality, safety in both social and natural environments, facility and management safety, destination image, and choice, and how these factors collectively impact satisfaction with the tourism experience and subsequent intention to revisit among tourists in Thailand. The research seeks to gain insights into the decision-making processes of tourists in Thailand. Design/Methodology/Approach – Employing a mixed-method approach, this study utilizes both primary and secondary data collection techniques. The sample comprises 390 respondents, consisting of tourists visiting Thailand. Additionally, this research integrates five theoretical frameworks from prior studies to develop a comprehensive conceptual framework. Findings – The study seeks to identify the determinants and characteristics influencing tourists’ intention to revisit. It further examines the significance of destination image, choice, and satisfaction with the tourism experience in shaping tourists’ intention to revisit. Research Limitations/Implications – It is acknowledged that the quantitative methodology employed in data collection may not fully capture all dimensions of tourists’ perceptions. Furthermore, the scope of this study is limited to tourists visiting Thailand from various regions worldwide. Originality/value – This study contributes to the understanding of the factors influencing tourists’ perception of quality, safety, destination image, and satisfaction, ultimately impacting their intention to revisit Thailand. Keywords – Tourist perceived quality, safety in social and natural environments, facility and management safety, destination image, choice, satisfaction with tourism experience, intention to revisit. Paper type – Research paper JEL classification code – M11, M14, M16, M10